ANALISIS PEMASARAN JERUK GERGA DI KECAMATAN RIMBO PENGADANG KABUPATEN LEBONG - Gracia Gabrienda; Fery Murtiningrum; Hefri Oktoyoki (LPPM UNIVERSITAS BINA INSAN, 2021)
Since citrus farming in Lebong Regency, Bengkulu Province, has begun to expand, this study is necessary to determine how the marketing channels and factors that affect the marketing margins of Gerga oranges in Rimbo Pengadang District, Lebong Regency. The marketing channel descriptive analysis was used as the analytical tool, and it describes the overall data collected. Multiple linear regression analysis with the formula Y = a + b1x1 + b2x2 + b3x3 + e is used to assess the variables that influence marketing margins. The marketing channel for gerga oranges in Rimbo Pengadang Village has 3 channel patterns, namely: farmers → retailers at village level → consumers, farmers → urban-level retailers → consumers, farmers → retailers at city level → consumers. It is well recognized that the three variables of sales volume, selling price, and marketing costs all influence marketing margins at the same time, resulting in a coefficient of multiple linear determinatio.